Melatonin Participates in Selenium-Enhanced Cold Tolerance of Cucumber Seedlings - Yang, Ning; Sun, Kaining; Wang, Xiao; Wang, Kean; Kong, Xianghua; Gao, Jianwei; Wen, Dan (Frontiers in Plant Science, 2021)
Melatonin is an important and widespread plant hormone. However, the underlying physiological and molecular mechanisms of melatonin as a secondary messenger in improving cold tolerance by selenium are limited. This study investigated the effects of selenite on cold stress of cucumber seedlings. The results showed that exogenous application of selenite improved cold tolerance of cucumber seedlings, which was dependent on the concentration effect. In the present experiment, 1 μM of selenite showed the best effect on alleviating cold stress. Interestingly, we found that in the process of alleviating cold stress, selenite increased the content of endogenous melatonin by regulating the expression of melatonin biosynthesis genes (TDC, T5H, SNAT and COMT). To determine the interrelation between selenite and melatonin in alleviating cold stress, melatonin synthesis inhibitor p-chlorophenylalanine and melatonin were used for in-depth study. This study provides a theoretical basis for cucumber cultivation and breeding.